Exploration of Teaching Reform and Innovation in Vocational Planting Majors Based on the Internet - Zhang, Deliang (Journal of Theory and Practice of Contemporary Education, 2023)
The continuous development of the Internet not only has a huge impact on social production activities, but also gradually changes the conduct of education work. The implementation of teaching work in vocational planting majors is mainly aimed at conveying more agricultural talents to society. With the proposal of the "Internet+Modern Agriculture Action", vocational planting majors should also consider the impact of the Internet on teaching work and reform and innovate their teaching work. This article takes the teaching of secondary vocational planting majors as the research object. From the perspective of the Internet, based on a large number of relevant literature and previous teaching experience, it briefly introduces the current situation of secondary vocational planting majors teaching, and then proposes innovative measures for teaching reform of secondary vocational planting majors based on the Internet. It is expected to provide more ideas for the high-quality development of secondary vocational planting majors teaching work.